Improved Stability and Performance of Surface Acoustic Wave Nanosensors Using a Digital Temperature Compensation - Balashov, S. M.; Rocha, J. M.; Hurtado, M. R. F.; Prestes, J. A. L.; de Campos, A. F. M; Moshkalev, S. A. (Frontiers in Sensors, 2021)
Surface Acoustic Waves (SAW) sensors are known to be an excellent choice for the measurement of a small concentration of analytes in gas mixtures. The use of this type of sensor has been limited until now in the industrial environment due to the sensitivity of its response to temperature variations. To overcome this problem, thermal stabilization of equipment is normally used. We propose here a simple procedure of compensation of thermal drift in SAW sensors, allowing the measurements to be performed in temperature intervals of up to 20 degrees without any thermal stabilization of the sensitive element of a sensor. By monitoring the temperature of the key points of the sensor and applying the proposed polynomial compensation, it is possible to reduce the influence of thermal instabilities of the ambient temperature to the response more than four times. The method is illustrated by a temperature compensated SAW humidity sensor with a graphene oxide nanofilm as water molecules’ sensitive element. The results show enhanced performance of the sensor over a large temperature interval.